2022
DOI: 10.3390/insects13100865
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Gardens Are Local Hotspots for Urban Butterflies in Arid Environments

Abstract: Urban areas are proliferating quickly around the globe often with detrimental impacts on biodiversity. Insects, especially pollinators, have also seen record declines in recent decades, sometimes associated with land use change such as urbanization, but also associated with climate changes such as increased aridity. How these various factors play out in attracting and sustaining species richness in a complex urban matrix is poorly understood. Urban botanical gardens may serve as important refugia for insect po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…was present in the WP and all three ex situ populations. Although botanical gardens and urban areas are usually considered pollinator hotspots due to the high diversity of plants and flowers (Prudic et al, 2022;Theodorou et al, 2020), we observed only two pollinator species in SP, which is located in a large botanical garden in a metropolitan city. However, the pollinator visiting frequency in SP was significantly increased, probably because the warmer and wetter environment there makes pollinators more active (Rohde & Pilliod, 2021).…”
Section: Plant-pollinator Interactionmentioning
confidence: 64%
“…was present in the WP and all three ex situ populations. Although botanical gardens and urban areas are usually considered pollinator hotspots due to the high diversity of plants and flowers (Prudic et al, 2022;Theodorou et al, 2020), we observed only two pollinator species in SP, which is located in a large botanical garden in a metropolitan city. However, the pollinator visiting frequency in SP was significantly increased, probably because the warmer and wetter environment there makes pollinators more active (Rohde & Pilliod, 2021).…”
Section: Plant-pollinator Interactionmentioning
confidence: 64%
“…Insectivorous bats are unlikely to expand their diet to the same extent as, for instance, fruit bats, other mammals, and birds, since arthropod diversity have been found to be lower in urban environments (Chatelain et al., 2023). However, without feces analysis of the studied bats, we are not able to confirm whether urban‐dwelling bats might be expanding their dietary diversity by relying on a higher diversity of urban arthropods associated with exotic plants (Prudic et al., 2022). Such fecal analysis could provide valuable insights into their actual diet composition, shedding light on potential dietary adaptations in response to urban environments.…”
Section: Discussionmentioning
confidence: 78%
“…While many bat species are thriving and reproducing in urban environments, some bats may still be challenged by finding food in areas where resources may be scarcer or unevenly distributed. Most bat species are insectivores primarily targeting nocturnal prey (Fenton & Simmons, 2014) that in urban areas might be less abundant and patchily distributed in specific “hotspots” such as parks, cemeteries, or areas illuminated by floodlights (Merckx & Van Dyck, 2019; Piano et al., 2020; Prudic et al., 2022; Straka et al., 2021). Thus, to meet their energy needs, urban, insectivorous bats may have to fly longer distances to several, smaller foraging sites (Geggie & Fenton, 1985; Voigt et al., 2020) but may rely less on conspecifics to find their prey in a habitat with predictable food sources (Roeleke et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation measures targeted at supporting insect populations should strive to maintain a large habitat patch size, good patch quality, reduce patch isolation [40], and reduce climate change to allow for maximum time for species adaptation [25]. In addition, ensuring reserves that can provide microclimates and refugia, such as those found in botanical gardens, may also help mitigate against the effects of climate change [41].…”
Section: Discussionmentioning
confidence: 99%